HUBUNGAN ANTARA TEKANAN DAN KEPUASAN KERJA DALAM KALANGAN KAKITANGAN JABATAN HAL EHWAL AGAMA ISLAM NEGERI SABAH (JHEAINS) BEAUFORT, SABAH - Abdul Ghaffar, Nahar Khayrah; Aripin, Siti Nazurulaina (Jurnal ’Ulwan, 2023)
This study aims to examine the relationship between stress and job satisfaction among JHEAINS staff in Beaufort, Sabah. A total of 30 respondents were selected based on a simple random method. The research instruments used are the Workplace Stress Scale (WSS) which is a questionnaire that measures the level of stress and the Minnesota Satisfaction Questionnaire - Short Form (MSQ) which is to measure the level of job satisfaction of the respondents. The data obtained were analysed in the form of descriptive and inferential statistics using the Statistical Package for Social Science (SPSS) version 26. The results of the study obtained based on Pearson’s correlation analysis showed that there was a significant relationship between stress and job satisfaction in which the value of r (30) = .439, k .05. In addition, the results of the study found that there is no difference in pressure based on gender where t (30) = -.349, k .05. The results of the last hypothesis also show that there is no difference in job satisfaction based on gender where t (30) = .325, k .05. Some recommendations for action and further studies are also recommended for future studies. Therefore, the researcher hopes that this study can help workers, especially civil servants, in dealing with stress at work so that it does not lead to any problems in the future.